2023
DOI: 10.1038/s41467-023-37709-0
|View full text |Cite
|
Sign up to set email alerts
|

Smart thrombosis inhibitors without bleeding side effects via charge tunable ligand design

Abstract: Current treatments to prevent thrombosis, namely anticoagulants and platelets antagonists, remain complicated by the persistent risk of bleeding. Improved therapeutic strategies that diminish this risk would have a huge clinical impact. Antithrombotic agents that neutralize and inhibit polyphosphate (polyP) can be a powerful approach towards such a goal. Here, we report a design concept towards polyP inhibition, termed macromolecular polyanion inhibitors (MPI), with high binding affinity and specificity. Lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…We found that our lead compound, MPI 8, was an effective thromboprotective agent in multiple mouse models of arterial and venous thrombosis, while showing no toxicity and, unlike the UHRA compounds, no prolongation of tail bleeding time even at very high doses. 62 This validated the "switchable" protonation state concept as a safer way of inhibiting polyP in vivo.…”
Section: Polyp As An Antithrombotic Targetmentioning
confidence: 64%
See 2 more Smart Citations
“…We found that our lead compound, MPI 8, was an effective thromboprotective agent in multiple mouse models of arterial and venous thrombosis, while showing no toxicity and, unlike the UHRA compounds, no prolongation of tail bleeding time even at very high doses. 62 This validated the "switchable" protonation state concept as a safer way of inhibiting polyP in vivo.…”
Section: Polyp As An Antithrombotic Targetmentioning
confidence: 64%
“…More recently, much more biocompatible dendrimer-like agents have been developed that are relatively selective for polyP, and are potent polyP inhibitors that avoid the toxicity of conventional cationic dendrimers. 62 These later-generation dendrimer-like molecules also protect mice against experimentally induced venous and arterial thrombosis, but without prolonging the tail bleeding time or toxicity. Future studies will be required to determine whether these novel agents that target polyP, NETs, or RNA can be translated into human therapeutics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has also demonstrated the antithrombotic effects of macromolecular polyanion inhibitors (MPI) in mouse models. Similar to other inhibitors, these polyP inhibitors do not increase bleeding [35 ▪▪ ]. Moreover, infusion of a recombinant bacterial exopolyphosphatase (PPX), which specifically degrades polyP longer than 35 P i units, or a variant of PPK lacking enzymatic activity but still capable of binding to the polymer, was shown to interfere with FXII activation and thrombosis, while preserving hemostasis [18].…”
Section: Polyphosphate In Coagulation and Thrombosismentioning
confidence: 95%
“…More importantly, phosphatases may also remove phosphates from other physiologically important compounds such as adenosine diphosphate, and thus bring about uncertainties. 161…”
Section: Antithrombotic Agents Targeting Polypmentioning
confidence: 99%